Silicone hydrogel contact lens surface analysis by atomic force microscopy: shape parameters - Giraldez, M. J. (2011)
spikes and troughs. Shape parameters as kurtosis (Rku) and skewness (Rsk) serve to distinguish between two profiles with the same Ra. They have been reported in many biomedical fields, but they were no applied to contact lenses before. The aim of this study is to analyze surface properties of four silicone hydrogel contact lenses (CL) by Atomic Force Microscopy (AFM) evaluating Ra, Rku and Rsk. Methods: CL used in this study were disposable silicone hydrogel senofilcon A, comfilcon A, balafilcon A and lotrafilcon B. Unworn CL surfaces roughness and topography were measured by AFM (Veeco, multimode-nanoscope V) in tapping mode™. Ra, Rku and Rsk for 25 and 196 μm2 areas were determined. Results: Surface topography and parameters showed different characteristics depending on the own nature of the contact lens (Ra/Rku/Rsk for 25 and 196 μm2 areas were: senofilcon A 3,33/3,74/0,74 and 3,76/18,16/1,75; comfilcon A: 1,56/31,09/2,93 and 2,76/45,82/3,60; balafilcon A: 2,01/33,62/-2,14 and 2,54/23,36/-1,96; lotrafilcon B: 26,97/4,11/-0,34 and 29,25/2,82/-0,23). In lotrafilcon B, with the highest Ra, Rku showed a lower degree of peakedness of its distribution. Negative Rsk value obtained for balafilcon A showed a clear predominance of valleys in this lens. Conclusions: Kku and Rsk are two statistical parameters useful to analyse CL surfaces, which complete information from Ra. Differences in values distribution and symmetry were observed between CL.